Egg Quality, Fertility and Hatchability of Laying Quails Fed Diets Supplemented with Organic Zinc, Chromium Yeast or Mannan Oligosaccharides - El-Samee , Laila D. Abd; El-Wardany, I.; Ali, Nematallah G.; Abo-El-Azab, O.M. (International Journal of Poultry Science, 2012)
The aim of this study was to investigate the effect of supplementing diets of laying Japanese quails (n = 250; 8 wk of age) with bioplex zinc, chromium yeast or Mannan Oligosaccharides (MOS) on egg weight, egg quality, fertility, hatchability and hatching chick weight. Diets were a basal diet or the basal diet supplemented with 20 mg bioplex zinc (Zn1), 40 mg bioplex zinc (Zn2), 600 mg Cr yeast (Cr1), 1200 mg Cr yeast (Cr2), 1.0 g MOS, Zn1 plus MOS, Zn2 plus MOS, Cr1 plus MOS or Cr2 plus MOS. Egg weight tended to be higher (p = 0.188) with the tested supplements compared to the control. Egg quality was not affected by the studied supplements. The high zinc diet or Cr2+MOS diet tended to improve egg fertility, while Zn1, Zn1+MOS or Zn2+MOS diets improved egg hatchability (p<0.001). The high Cr diet and Cr2+MOS diet tended to increase hatching chick weight. It is concluded that, supplementation of laying Japanese quail diets with bioplex zinc, chromium yeast or mannan oligosaccharides tended to increase egg weight without affecting egg quality. Supplementing the diets with 40 mg bioplex zinc or 1200 mg chromium yeast + 1.0 g mannan oligosaccharides/kg tended to improve egg fertility and hatching chick weight. Supplementing the diets with bioplex zinc up to 40 mg/kg alone or in combinations with 1.0 g mannan oligosaccharides/kg improved egg hatchability significantly.